Optimalisasi Teknologi Digital dalam Pembelajaran untuk Guru SD Negeri 013 Desa Perkebunan Sungai Parit Kecamatan Sungai Lala Kabupaten Indragiri Hulu - Julinaldi, Julinaldi; Putri, Meilya Karya; Agustin, Sri; Erny, Erny; Guntur, Sri; Mauliantino, Boby (Universitas Pahlawan Tuanku Tambusai, 2025)
This community service activity was conducted to address the challenges of digital technology utilization in learning at SD Negeri 013, Desa Perkebunan Sungai Parit, where the use of digital devices and applications was limited. The method involved direct socialization, training, and mentoring for teachers using a participatory approach over two months. The results showed significant improvements in teachers’ understanding of digital technology (from 45% to 85%), their ability to operate digital learning applications (from 30% to 80%), and the transformation of teaching methods into more interactive and technology-based approaches (from 25% to 75%). Obstacles such as limited devices and unstable internet were addressed through additional training and alternative teaching methods. These results highlight the importance of continuous training and intensive mentoring to optimize digital technology use, thereby enhancing the quality of education in elementary schools.